Dinamika Kejahatan Terorisme di Indonesia : Kajian Atas Tragedi Bom Kampung Melayu dan Upaya Aktualisasi Bela Negara - Siti Syafa Az Zanubiya; Adinda Kusumaning Ratri; Slamet Tri Wahyudi (International Forum of Researchers and Lecturers, 2025)
The Kampung Melayu bombing tragedy in May 2017, which involved a suicide bombing, highlighted new dynamics in terrorism crimes in Indonesia in terms of attack patterns, targets, and impacts. The study of the Kampung Melayu bombing case can provide a clearer picture of how terrorism crimes develop and how state defense strategies can be optimized to prevent similar threats in the future. This study aims to analyze the dynamics of terrorism development in Indonesia, especially through the Kampung Melayu bombing case study, and explore the implementation of the concept of state defense as a collective response to the threat. The research method used is normative juridical, with a statutory approach and analysis of relevant legal concepts. Therefore, it is important to examine more deeply how the crime of terrorism develops by examining it from the legal and social aspects. This study concludes that the eradication of terrorism must be a shared responsibility between the government and society by integrating legal policies and the implementation of state defense in order to strengthen national resilience.